Judicialização da saúde e assistência farmacêutica no pós-88: efeitos na administração pública municipal do Estado de São Paulo - Novaes, Natália Fazano (2012)
The growth of political conflicts taken to the Brazilian Judiciary power, has caused issues such as health rights and drug distribution policies to be now decided in the Brazilian courts; such decisions produce a variety of effects to the ongoing public policies. According to the Federal Constitution of 1988, the right to health was added a legal approach apart from the political and technical ones. This duplicity generates different interpretations, execution and effectiveness for the health rights in the public powers. Given the need to develop public policies for the effectiveness of health rights, in a universal and egalitarian way, as well as the role played by the Judiciary in distributive justice, many consequences and difficulties are created for the public administration and pointed out by the legal doctrine. This work proposes to verify the specific effects generated by the interpretation and participation of the judicial power into the Pharmaceutical public policies of SUS (Sistema Único de Saúde/Unify Heath System) in the municipalities of São Paulo. In this context, the lawsuits and court decisions produce different effects in the Public Administration (responsible for public policies of pharmaceutical assistance). This participation and its effects may be useful and positive, because it assists in the protection of social rights by promoting and structuring public polices; although it may also provide disastrous consequences in the Public Administration performance. The hypothesis proposed in this work intends to demonstrate that when the judicial power condemns the municipal Public Administration on the Pharmaceutical Assistance policies it does not generates positive accomplishes, but negative consequences and difficulties for the public health management of SUS. In that way, the present research seeks to identify some of the possible effects of judicialization process in health rights and drug distribution policies in the municipalities in the State of São Paulo.